Penerapan Model Pembelajaran Behavioristik Untuk Meningkatan Sosial Emosional Di TK Darul Hijrah Al-Amin Samarinda - Fadillah, Nur Rahma; Hikmah, Nur; Julaiha, Ayga Nuari; Annisa, Nur; Della, Laili Anggraini Putri; Muspiyah, Muspiyah; Rachmawaty, Risma (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Social-emotional development is a vital aspect of early childhood growth, influencing children's abilities to interact, manage emotions, and build social relationships. This article explains the implementation of the behavioral learning model to enhance children's social-emotional behaviors using collective action research (CAR) techniques at Darul Hijrah Al-Amin Kindergarten. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The findings demonstrate that applying the behavioral learning model through positive reinforcement, appropriate stimulation, and consistent behavior management can significantly improve children's social and emotional skills. The children showed enhanced abilities in communication, cooperation, and recognizing and managing their emotions. This study confirms that the behavioral learning model can be an effective approach to supporting the social-emotional development of young children. This article aims to assist educators in developing learning strategies that holistically support children's growth and development.